107 Influence of chronic melatonin supplementation on bovine testis physiology. (28th November 2020) - Littlejohn, Brittni P; Mercer, Kayla B; Bowers, Karrigan J; Messman, Riley D; Contreras-Correa, Zully; Reid, Dana; Feugang, Jean; Vann, Rhonda C; Lemley, Caleb O
Abstract: The objective was to evaluate the influence of melatonin supplementation on bovine testis biometrics, thermoregulation, and blood flow in two age groups. Mature and peri-pubertal bulls received four subdermal 24 mg melatonin implants (MEL; n = 5 and n = 6, respectively) or no implants (CON; n = 5 and n = 6, respectively) every 30 ± 4 d for 120 ± 5 d. Body weight, scrotal circumference (SC), testes temperature (average temperature of left and right testes as quantified with thermal imaging), and total testicular artery blood flow (TBF; total blood flow to left and right testes as measured with Doppler ultrasonography) were evaluated on d 60, 90, and 120 ± 4. On d 120, peri-pubertal bulls were castrated and total testes weight (TTW) determined. Data were analyzed using MIXED procedures of SAS specific for repeated measures with treatment, time, and the interaction as fixed effects and sire (peri-pubertal only) as a random effect. On d 120, peri-pubertal bull data were analyzed using MIXED procedures of SAS with treatment as a fixed effect and sire as a random effect, and relationships of TBF, SC, TTW, testes temperature, and ambient temperature assessed using CORR procedures of SAS. Body weight, testes temperature, TBF, and TBF as a proportion of SC changed over time in peri-pubertal (P < 0.05) but not mature (P > 0.05) bulls. On d 120, TBF was increased (P = 0.05) and TBF as a proportion of TTW tended (P = 0.10) to be increased in MEL (95.48 ± 14.63 mL/min and 0.29 ± 0.03 mL/min*g, respectively) compared to CON (65.06 ± 15.10 mL/min and 0.21 ± 0.03 mL/min*g, respectively) peri-pubertal bulls. TBF was positively correlated with SC (r = 0.59; P = 0.04) and TTW (r = 0.66; P = 0.02). Ambient temperature was positively correlated with testes temperature (r = 0.78; P < 0.01). No other differences were identified (P > 0.05). Limited alterations in testis physiology were observed in melatonin-supplemented bulls.